Proposta de contribuição para a gestão omnicanal no varejo brasileiro - Bronholo, Elisabete Furtado (2018)
The omnichannel strategy has been characterized as the most recent evolutionary stage of the study of distribution channels. Nevertheless, companies lack knowledge on the topic of omnichannel management and its practices and concepts. In her search for references, the author found that the literature focuses more on the perspective of experience, the evolutionary process, distinctions between multichannel and omnichannel, rather than omnichannel tactics and practices. Thus, furthering understanding of the activities performed can help companies develop effective omnichannel management. The aim of this study is to identify practices and recommendations that contribute to omnichannel management in the Brazilian retail market. To this end, the study employed a qualitative methodology based on interviews with fifteen companies that operate with multiple channels, and applied the U.S. Omnichannel Customer Experience Index (OcCEI) tool of the Omnichannel Report Card study designed by IBM Commerce. The study assesses retail omnichannel practices in seven areas of analysis: Online and Digital Experience, Physical Store Experience, Fulfillment/Delivery Flexibility, Mobile Website/App, Integrated Marketing and Pricing, Call Center/Customer Service and Social Media. The analysis took into account individual companies and groups of companies according to their size/number of stores. The results show the following omnichannel practices: inspiring leadership, digital mentality/cultural change, customer first, management of the shopping journey as a process, integration and cross-management, transparency of customer data and that of stocks in all points of contact of the business, synthesized as 360o transparency, online maturity, logistical mastery and curatorship. It is hoped that this study will contribute to the identification of commonalities and differences regarding activities performed by companies with a view to omnichannel management, identifying strengths and areas for potential improvement. The study is also expected to provide to the academic milieu environment information on the omnichannel stage of fifteen companies operating in Brazil that are relevant in their markets and areas of activity.